Violation of the constitutional right to motivate sentences by determining civil reparation in organized crime, La Libertad 2018-2020 (SCIÉNDO INGENIUM, 2022)
The general objective of this research is to establish how the determination of civil compensation in organized crime violates the constitutionally guaranteed content of the right to reason for sentences, La Libertad Superior Court of Justice, 2018-2020. Contains mixed approach and correlational design (explanatory sequential). The qualitative sample is of nine convictions for organized crime, La Libertad 2018-2020, the quantitative sample is of fifteen prosecutors specialized in Organized Crime and ninety-four criminal lawyers in the region. The SPSS-V23 statistical software was used to process information from the record sheet, checklist and survey instruments. As a result, there is direct and significant influence, Pearson coefficient R=0.917 and Spearman Rho= 0.595, influence of 84.1% and 69% (15.9% and 39% other factors); accepting as a hypothesis that the determination of civil compensation in organized crime directly and significantly violates the constitutionally guaranteed content of the right to reason for sentences, Superior Court of Justice of La Libertad 2018-2020. This reality is common at the national level, requiring sufficient jurisprudence to the essential content of the motivation of sentences, with greater development in correctly identifying and quantifying the damage, promoting and consolidating criteria for determining civil liability, seeking due process.
Keywords: Civil reparation; Organized crime; Motivation of sentences